PERLINDUNGAN HUKUM BAYI MELALUI PEMBERIAN ASI EKSKLUSIF DALAM PRESPEKTIF UNDANG-UNDANG NOMOR 36 TAHUN 2009 TENTANG KESEHATAN - Edy Nurcahyo; Siti Khuzaiyah (STIH Putri Maharaja, 2018)
The legal research aims to describe legal protection for exclusive breastfeeding for babies in the prespective of Law Number 36 of 2009 concerning Health. The research method is normative legal research. The main data source used is literature. The author uses the statutory approach because it adapts to the legal material being studied, then analyzed with qualitative analysis. The result of the study shows that legal protection for exclusive breastfeeding for infants has obtained public law protection. Indonesia has implemented the International Code of Marketing of Breastfeeding-Milk Substitutes through a national policy to support the exclusive breastfeeding program, namely by the prohibition of advertising of infant formula milk either through print or electronic media.